60th Anniversary of Turkish Librarianship Journal - Tayfun Gülle (Türk Kütüphaneciliği)
This article deals with the symposium named “60 Years of Professional and Scientific Communication” organized on October 12, 2012 byTurkish Librarianship Journal, which celebrates its 60th anniversary in 2012. Decisions on preparing an action plan for internationalisation of the Journal and sharing it regularly with colleagues were taken at the event which included a plaquet ceremony for previous editors, a documentary about the 60th anniversary of the journal, a panel on “Publishing Journals in The Field of Social Sciences in Turkey and in the World”, an exhibition of selection from the journal archive, a forum on the journal and a closure cocktail party.